EMBRACE – A modular chair - Risberg,Renée (Diploma work, 2023)
This Bachelor’s degree project investigates how to create a modular chair system. It should let the consumer combine different parts to create a chair that fits their home, style and needs. The focus is on how a low number of parts can be used in different ways to create differentcombinations. It should also be easy to replace and recycle all parts when needed. This document shows the full design process from the initial idea and background to the final prototype. The final result is a modular chair that changes with you through life.
Keywords: Chair; Dining Chair; Modularity; Sustainability; Design for Disassembly; Furniture Design; Modular Chair